Grice’s Maxim in Humor Conversation of Yoo Bro Meme Comic - Milda Sari; Susilo; Effendi Limbong (English Department, Faculty of Teacher Training and Education, Mulawarman University, 2019)
Humor is funny thing which is made by creativity, interest, and critic to entertain the reader. Through humor violating maxims may occur. This studies concerns on Grice's Maxim in Humor Conversation of Yoo Bro Meme Comic. The main focus of the researcher is to analyze violating maxims use in the conversation of yoo bro meme comic. The purposes of this study are; (1)To identify and classify kinds of maxim are disobeyed in humor conversation of Yoo bro meme comic and (2)To explain how violated maxim generates a sense of humor in Yoo bro meme comic. The design of this study was descriptive qualitative which describes what the data shows. The researcher was the key instrument because she directly involved collecting and analyzing the data in this study. The researcher conducted the study and took the data from website https://me.me/t/yoo-bro. The source of data is 48 conversations. This study used Miles and Huberman’s flow model for analyzing. To identify types of violating maxim and how violating maxim generate sense of humor, researcher applied theory proposed by Grice (1975) as guideline. The result reveals that: (1)There are four types violating maxims found in the conversations of Yoo Bro Meme Comic, namely, violating maxim of quantity, violating maxim of quality, violating maxim of relation, and violating maxim of manner. The most frequent type of violating maxim used by the subject is violating the maxim of quality which occurred 22 times 36.07% of the total violations. The second most common was violating the maxim of relation, this happened 19 times or 31.15% of all occurrences. Violating the maxim of quantity came in third with 22.95% or 14 occurrences. The least frequent type of violating maxims to be used in the conversation of Yoo Bro Meme Comic is violating maxim of manner. It happened 6 times or 9.83% of the total occurrences. (2) To generate sense of humor in yoo bro meme comic, the result showed that behind of violating maxim of quantity the speaker being uninformative, the speaker did not attempt to go truthful behind violating maxim of quality, the speaker being irrelevant behind violating maxim of relation and being unclear behind violating maxim of manner